Toll‐Interleukin 1 Receptor domain‐containing adaptor protein positively regulates BV2 cell M1 polarization. (24th May 2016) - Gong, Leilei; Wang, Hanxiang; Sun, Xiaolei; Liu, Chun; Duan, Chengwei; Cai, Rixin; Gu, Xingxing; Zhu, Shunxing
Abstract: Microglial activation, including classical (M1) and alternative (M2) activation, plays important roles in the development of several central nervous system disorders and promotes tissue reconstruction. Toll‐like receptor (TLR)4 is important for microglial polarization. TIR domain‐containing adaptor protein (TIRAP) is an intracellular adaptor protein, which is responsible for the early phase of TLR4 activation. The role of TIRAP in BV2 cell M1 polarization is still unknown. In this study, we showed that TIRAP expression is greatly elevated in lipopolysaccharide (LPS)/interferon (IFN)‐γ‐treated microglia. TIRAP overexpression promoted BV2 microglial M1 polarization by increasing M1‐related marker production (inducible nitric oxide synthase, CD86, interleukin‐6, interleukin‐1β and tumour necrosis factor‐α). In contrast, TIRAP knockdown prevented M1‐related marker production. Mechanistically, TIRAP could interact with TNF Receptor‐Associated Factor 6 (TRAF6) to increase M1‐related marker production in TIRAP overexpressed and LPS/IFN‐γ‐treated BV2 cells. In addition, silencing of TIRAP effectively inhibited the activation of the Transforming Growth Factor‐Beta‐Activated Kinase 1/I‐Kappa‐B Kinase /Nuclear Factor of Kappa Light Polypeptide Gene Enhancer in B‐Cells (TAK1/IKK/NF‐κB) signalling pathway and the phosphorylation of Akt and mitogen‐activated protein kinases, which were activated by LPS/IFN‐γ stimulation. Thus, our results suggest that TIRAP positively regulated BV2 microglial M1 polarization through TLR4‐mediated TAK1/IKK/NF‐κB, mitogen‐activated protein kinases and Akt signalling pathways. Abstract : In this study, we found that TIRAP expression is elevated by LPS/IFN‐ γ in microglia cells. It was observed that TIRAP could increase the protein and mRNA level of M1‐related markers, which were decreased by silencing of TIRAP. We also demonstrated that TIRAP promotes the microglia M1 polarization through the TLR4 signaling pathway.